2017
DOI: 10.1007/s00345-017-2043-3
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal ultrasound guided prostate biopsy in the era of increasing fluoroquinolone resistance: prophylaxis with single-dose ertapenem

Abstract: A single-dose of 1 g of intravenous ERT applied 1 h before a scheduled transrectal prostate biopsy is a safe option and provides effective protection against infection-related complications arising from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In this context, we confirmed the infection rate of almost zero of recent single‐centre studies [12,24]. Several groups suggested upfront antibiotic augmentation [7,25], even using carbapenem‐based prophylaxis [26,27], to face the alarming worldwide increase of post‐procedural sepsis following TR biopsies [3–6]. Given the global warnings on antibiotic overuse, the TP biopsy infection rate should be regarded as a major reason to prefer the TP over the TR approach.…”
Section: Discussionsupporting
confidence: 80%
“…In this context, we confirmed the infection rate of almost zero of recent single‐centre studies [12,24]. Several groups suggested upfront antibiotic augmentation [7,25], even using carbapenem‐based prophylaxis [26,27], to face the alarming worldwide increase of post‐procedural sepsis following TR biopsies [3–6]. Given the global warnings on antibiotic overuse, the TP biopsy infection rate should be regarded as a major reason to prefer the TP over the TR approach.…”
Section: Discussionsupporting
confidence: 80%
“…In the first 7 days following the procedure, there were no documented new infections in either group, indicating that there was no introduction of bacteria via the needle biopsy. This is consistent with previous literature and supports the adoption of the TP route rather than the TR route as a safer method of biopsy by avoiding fecal contamination 2,3,8 . Unfortunately, there was an infectious complication relating to a patient suffering from AUR on day 9 following the operation.…”
Section: Discussionsupporting
confidence: 90%
“…This has resulted in broad‐spectrum carbapenems being used in patients preprocedure and postprocedure 3 . With the introduction of TPBx, there has been a drastic reduction in the rates of procedure‐related infection 8 . Compared with TPBx, UTI is 5.4 times more common when TRUS biopsy is performed, with further increased risk if greater than 12 cores are sampled 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators evaluated cephalosporins such as ceftriaxone as an alternative with sufficient relative to flouroquinolones as antibiotic prophylaxis for transrectal prostate biopsy [16,27,28]. In addition, Seitz et al [29] showed a significant reduction in infectious complication with single-shot ertapenem versus ciprofloxacin antibiotic prophylaxis (0.8% vs 14.5%). However, it is noteworthy that cephalosporins and carbapenems such as ceftriaxone and ertapenem need to be given intravenously or intramuscularly.…”
Section: Discussionmentioning
confidence: 99%